DEVELOPMENT OF COMICS LEARNING MEDIA ON THE ORIGINS OF MOUNT KELUD USING FICTION STORY MATERIAL FOR CLASS 4 STUDENTS OF SDN TAROKAN 3 - Armadhani, Rio; Zaman, Wahid Ibnu; Wahyudi, Wahyudi (JURNAL EDUSCIENCE, 2023)
This research produces a new product that can bring digital learning experiences to elementary schools in the form of learning media and can solve several existing problems. This research focuses on solving learning problems that are still teacher-centered, there is no variety of learning media, and learning facilities are incomplete. The aims of this research are, (1) to produce valid products, (2) to produce practical products, (3) to produce effective products. This research uses the Research and Development (R&D) method with the development model by Borg & Gall. The subjects in this research were fourth grade students at SDN Tarokan 3. The results of this development research were: (1) comic media was declared valid by media experts with a validity percentage of 84.7%, (2) comic media was declared valid by material experts with a percentage of validity of 98.4%, (3) comic media was declared practical by the teacher with a practicality percentage of 97%, (4) comic media was declared effective with the N-gain test results showing an increase with an average value of 0.36 (medium increase ).Keywords: Learning Media; Comic; Fictional StoryAbstrak Penelitian ini menghasilkan suatu produk baru yang dapat membawa pengalaman pembelajaran digital ke sekolah dasar dalam bentuk media pembelajaran serta dapat menyelesaikan beberapa permasalahan yang ada. Penelitian ini berfokus pada menyelesaikan permasalahan pembelajaran yang masih berpusat pada guru, tidak terdapat variasi media pembelajaran, serta sarana pembelajaran yang belum lengkap. Tujuan dari penelitian ini adalah, (1) menghasilkan produk yang valid, (2) menghasilkan produk yang praktis, (3) menghasilkan produk yang efektif. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan oleh Borg & Gall. Subjek pada penelitian ini adalah siswa kelas IV SDN Tarokan 3. Hasil dari penelitian pengembangan ini adalah: (1) media komik dinyatakan valid oleh ahli media dengan persentase kevalidan sebesar 84,7%, (2) media komik dinyatakan valid oleh ahli materi dengan persentase kevalidan sebesar 98,4%, (3) media komik dinyatakan praktis oleh guru dengan persentase kepraktisan sebesar 97%, (4) media komik dinyatakan efektif dengan hasil uji N-gain menunjukkan peningkatan dengan nilai rata-rata sebesar 0,36 (peningkatan sedang).Kata Kunci: Media Pembelajaran; Komik; Cerita Fiksi